Cardiovascular events in crush syndrome: on-site therapeutic strategies and pharmacological investigations - Zhang, Meng-Wan; Tan, Fu-Qin; Yang, Jia-Rong; Yu, Jian-Guang (Frontiers in Pharmacology, 2024)
Crush syndrome often occurs after severe crush injury caused by disasters or accidents, and is associated with high mortality and poor prognosis. Cardiovascular complications, such as cardiac arrest, hypovolemic shock, and hyperkalemia-related cardiac dysfunction, are the primary causes of on-site death in crush syndrome. Prehospital evaluation, together with timely and correct treatment, is of great benefit to crush syndrome patients, which is difficult in most cases due to limited conditions. Based on current data and studies, early fluid resuscitation remains the most important on-site treatment for crush syndrome. Novel solutions and drugs used in fluid resuscitation have been investigated for their effectiveness and benefits. Several drugs have proven effective for the prevention or treatment of cardiovascular complications in crush syndrome, such as hypovolemic shock, hyperkalemia-induced cardiac complications, myocardial ischemia/reperfusion injury, ventricular dysfunction, and coagulation disorder experimentally. Moreover, these drugs are beneficial for other complications of crush syndrome, such as renal dysfunction. In this review, we will summarize the existing on-site treatments for crush syndrome and discuss the potential pharmacological interventions for cardiovascular complications to provide clues for clinical therapy of crush syndrome.